2005
DOI: 10.1038/nature04061
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Crooks fluctuation theorem and recovery of RNA folding free energies

Abstract: Atomic force microscopes and optical tweezers are widely used to probe the mechanical properties of individual molecules and molecular interactions, by exerting mechanical forces that induce transitions such as unfolding or dissociation. These transitions often occur under nonequilibrium conditions and are associated with hysteresis effects-features usually taken to preclude the extraction of equilibrium information from the experimental data. But fluctuation theorems 1-5 allow us to relate the work along none… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
1,124
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,008 publications
(1,161 citation statements)
references
References 28 publications
26
1,124
0
11
Order By: Relevance
“…(31), F corresponds to the work value W * for which P F (W * ) = P B (−W * ), as it has been verified through statistical sampling of nonequilibrium realizations made with identical time schedule in optical tweezers experiments 45 and numerical simulations. 46,47 However, for fast nonequilibrium realizations, a large amount of work, rather than in advancing the reaction coordinate, is dissipated as heat into the system.…”
Section: Steered Molecular Dynamicsmentioning
confidence: 77%
“…(31), F corresponds to the work value W * for which P F (W * ) = P B (−W * ), as it has been verified through statistical sampling of nonequilibrium realizations made with identical time schedule in optical tweezers experiments 45 and numerical simulations. 46,47 However, for fast nonequilibrium realizations, a large amount of work, rather than in advancing the reaction coordinate, is dissipated as heat into the system.…”
Section: Steered Molecular Dynamicsmentioning
confidence: 77%
“…However, values of changes in free energies, ΔΔG, between mutants with the same number of nucleotides do not depend on any stretching calculations. Thus, force unfolding can be particularly useful for determining changes caused by mutations, by binding ligands such as magnesium ions (Collin et al 2005), or by changing solvent.…”
Section: Crooks Fluctuation Theorem (Crooks 1999): Crooks Fluctuatiomentioning
confidence: 99%
“…The area under the lowest refolding curve is shown in blue. The measured mechanical work values were analyzed using Jarzynski's equality and Crooks fluctuation theorem (Collin et al 2005). Collin et al 2005).…”
Section: Kineticsmentioning
confidence: 99%
“…5 It was found that the peptide subunit cyclo [(-L-Phe-D-N-MeAla-) 4 -] adopts a flat-ring-shaped conformation, which energetically favors ring stacking and intermolecular hydrogen-bonding interactions over the nonassembled form by 4.0-5.6 kcal mol -1 , depending on the solvent. The free energy of the dimerization process is accessible via steered MD (SMD) simulations using Crooks theorem 16,17 in the form of the Jarzynski equality. [18][19][20] Understanding the behavior of a single peptide subunit at the hydrophobic/hydrophilic interface is crucial to the understanding of the mechanism of formation of a nanotube in a hydrated lipid bilayer.…”
Section: Introductionmentioning
confidence: 99%